Columnas Compuestas de Hormigón y Acero SRC, Sujetas a Flexocompresión Biaxial - Jaramillo, Jorge Ricardo Vintimilla (2018)
The work presented is based on experimental and theoretical analysis of SRC composite columns subjected to biaxial bending and axial compression, where the specification of American and European code criteria are used to calculate de load bending strength. The computer program to calculate the interaction diagram of biaxial bending and axial compression with inclined neutral axis is made in the software Matlab by using the fiber method, besides, the strength of the specimen is calculated. Users can design new frame sections and check the exist sections. To obtain the displacements and load curve, to calculate load contours and determination of the interaction family curves of the modeled sections. The destructive performance of the round and rectangle composite columns are made in the structures laboratory of EPN to obtain the results such as the buckling displacement at strong, weak and longitudinal direction measured with LVDT´S. Subsequently, the theoretical and experimental analysis results are made to demonstrate the reliability of the numeric model.Keywords: Composite Columns, Concrete, Steel